(3aGcgI GdNdaGA hoeaGcgI GdoXQaGAs - (3CMeO Hf eMeO Hf YHO Gddg Hf EHQGgje, CHh eMeO, TgGH GdOjf, GdeYQha HGHf nYnQrHTGg , J (B854 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEf Gddg GdebOS aj PGJg bO ChOY aj cd PQI ef eNdhbGJg s
(3BNQgG (B:s
(3hdabg eUfag ef ZjQ JQOO hdG JacQ eY JhRY GdHGd s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B122s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B75 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1216s
Keywords: (3GdCOHs